CERRAHPAŞA TIP FAKÜLTESİ KADIN-DOĞUM ANABİLİM DALINDA XX. YÜZYILDA UZMAN OLANLAR (1892-2000) - KAZANCIGiL, Aykut; AKSU, Feridun (Cerrahpaşa Medical Journal, 2014)
Background.- Obstetrics and Gynecologgy Department of Cerrahpaşa Faculty of Medicine is the first and the unique clinic which has ever been founded in Ottoman Empire by Besim Omer Pasha (Akahn) in 1892 under the name of "Veladethane" (meaning labor-in hospital) upon a decree of the Emperor. In 1909, it has been united with the disipline of Gynecology and transferred from its first building located in Demirkapı Sirkeci to Kadırga and following a change from Kadırga to Haydarpaşa in 1928. In 1930, after the great university reform of Atatürk, It has moved again from Haydarpaşa to Haseki. In 1966, from Haseki to Cerrahpaşa to its last residence. Convering all these years, ten residents from Sirkeci, 17 from Kadırga, 7 from Haydarpaşa, 195 from Haseki and 167 from Cerrahpaşa were graduated. In this documentary you will find the list of their diplomas and thesis that have been officially accepted from 1946 to the presenting time. Essentially, many clinics, departments and specialty hospitals have been founded in Turkish Republic by the graduates and their successors of this faculty which has anniversarried its 108 years as an Obstetrics and Gynecology Department.